Radicalization and de-radicalization between national and global jihadism: from the first Egyptian national jihadists to Al-Qaeda - Brzuszkiewicz, Sara (Lexington Books, 2024)
"In the past, a number of jihadists initiated processes of ideological de-radicalization and doctrinal revisions that transformed their stance towards violence. The book investigates the reasons why this does not happen among contemporary jihadists and posits that, once jihad ceased to be national and became global, it no longer had a set of features that made de-radicalization possible"--